Efeito da administração de Piracetam sobre os receptores muscarinicos e a atividade acetilcolinesterasica - Marinho, Marta Maria Fonteles (1990)
The effect of Piracetam adm 1 n i st r at i on (100 e 500mg/Kg, v.o.) during 1, 7 and 15 days on . the muscarinic receptor density (MRD) and acety1cholinesterase activity (AChE) was studied ín cerebral motor córtex of young and old rat s . It was observed that the acute treatment (24h) did not produce any effect on the MRD. On the other hand, the chronic treatment caused a significative increase ín the receptor density in the young animais (777,2fmol/mg protein) and the old ones (741,9fmol/mg protein) relative to their respective Controls (546,0 and 545,4fmol/mg protein) Scatchard analysis revealed an increase in the values of receptors maximal density (Bmax) and for the equilibrium dissociation constant (Kd) of the control groups of young (Bmax = 663,4fmol/mg protein; Kd = 0,45nM) and old rats (Bmax = 628,0fmol/mg protein; Kd = 0,47nM) in relation to young (Bm,„ = 961,9fmol/mg protein; Kd = 0,88nM) and old animais <Bm,u = 747,6fmol/mg protein; Kd - 0,84nM0 belonging to the group treated with Piracetam <500mg/Kg) during 1 week No alteration was seen in the acety1cho1inesterase activity in the two groups treated with Piracetam <500mg/Kg) during 1 week and also in the groups treated and pretreated before with Lithium. However at a small dose (100mg/Kg) the drug caused a significant decrease in enzyme activity In the "in vitro" experiments the addition of Piracetam in concentrations ranging from luM up to lmM did not modify the acety1cho1inesterase activity The addition of Piracetam "in vitro" showed that the drug doesnt interact directly with colinoceptíve sites discarding the possibility that a classic "up - regulation" phenomenon could explain the increase in MRD.